Proteoliposomes as a Method of Membrane Protein Immobilization for SPR-analysis with the Human CYP3A4 and CYB5A Interaction as an Example - Kaluzhskiy, L.A.; Yablokov, E.O.; Kisel, M.S.; Tumilovich, A.M.; Usanov, S.A.; Shkel, T.V.; Gnedenko, O.V.; Ivanov, A.S. (Biomedical Chemistry: Research and Methods, 2021)
Microsomal systems of human cytochrome P450 consist of three components, which are membrane proteins: cytochrome P450 hemoprotein (CYP), NADPH-dependent cytochrome P450 reductase (CPR), and a small regulatory heme-containing protein cytochrome b₅ (CYB5A). In the study of the cytochrome P450 system functioning the study of intermolecular interactions both with partner proteins and with possible drug prototypes is of great importance. Surface plasmon resonance (SPR) is a powerful and reliable tool for studying intermolecular interactions. However, there is a problem of immobilization of membrane proteins on the optical chip of the SPR biosensor. It is important to immobilize such proteins in native conditions with respect to the correct orientation of the protein globule to the surface of sensor. Previously, we have developed and described a method involving direct native immobilization of membrane proteins into a planar bilayer lipid membrane on the surface of a biosensor chip. At the same time, one of the commonly used approaches to working with membrane proteins using various methods is the construction of proteoliposomes containing membrane proteins. In this work, using CYP3A4 and CYB5A as protein partners, we evaluated two approaches to the creation of proteoliposomes: incorporation of a membrane protein into liposomes saturated with detergents and incorporation of a membrane protein into the forming proteoliposomes by the mechanism of micellar coalescence. The interaction of CYP3A4 with proteoliposomes obtained by incorporating CYB5A into detergent-saturated liposomes was shown. On the contrary, interaction between CYP3A4 and proteoliposomes containing CYB5A, obtained by the method of micellar coalescence, was not detected. Thus, it was shown that the incorporation of the membrane protein into liposomes saturated with a detergent was a more preferable method for working with an SPR biosensor as compared to the method of proteoliposomes formation by micellar coalescence. Detailed protocols for the creation of proteoliposomes and SPR-analysis can be useful to a wide range of researchers.